Marketing Strategy Analysis to Increase the Number of Medical Check-Up Patients at Sawahlunto Regional General Hospital - Asri, Asri; Rahardjo, Tri Budi W.; Nurminingsih, Nurminingsih; Agustin, Dinni (Journal of Ageing And Family, 2024)
Background : Sawahlunto Regional General Hospital (RSUD Sawahlunto) faces challenges in increasing the number of Medical Check-Up (MCU) patients. The number of MCU patients decreased from 416 in 2023 to 160 in 2024. In order to compete with other hospitals, an appropriate marketing strategy is needed to boost patient visits for MCU services and to strengthen RSUD Sawahlunto’s position as a trusted healthcare provider. This study aims to analyze marketing strategies that can be implemented to increase the number of MCU patients at RSUD Sawahlunto. The study identifies strengths, weaknesses, opportunities, and threats (SWOT) and evaluates the most effective segmentation, targeting, positioning (STP), and marketing mix strategies. This research uses a qualitative and quantitative approach with data collection techniques including in-depth interviews, observations, and document studies. The analysis is conducted using the SWOT method, Internal-External (IE) matrix, and Quantitative Strategic Planning Matrix (QSPM) to determine optimal marketing strategy alternatives. The results of the study show that several factors contribute to the low number of MCU patients at RSUD Sawahlunto, including a lack of effective promotion, limited additional services, and competition with other hospitals. Through SWOT analysis, key strategies were identified, such as strengthening digital marketing, establishing partnerships with companies for employee MCU services, and improving the quality of MCU services and facilities. The study concludes that an appropriate marketing strategy is essential to increase the number of MCU patients at RSUD Sawahlunto. By implementing an effective marketing mix—such as more aggressive promotions, improved customer service, and optimized pricing and distribution strategies—RSUD Sawahlunto can enhance its competitiveness in providing MCU services. Keywords: Medical Check-Up, Marketing Strategy, Hospital, Marketing Mix